Analysis of Educator Readiness in the Online Teaching Learning Process Using Naïve Bayes - Yuyun Yusnida Lase; Yulia Fatmi; Haryadi Haryadi; Arif Ridho Lubis; Santi Prayudani (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
This study discusses the readiness of educators in the online teaching and learning process. Samples of data were taken randomly as many as 100 (one hundred) people who were carried out using a questionnaire for educators at the junior high school level in the city of Medan. The variables used in the research are human resources, facilities and infrastructure, skills in applying technology, time management in online learning, the assessment process. Data processing and data analysis using nave Bayes algorithm. This algorithm is very well used for the process of classifying large amounts of data. The reason for using the nave Bayes algorithm in processing and analyzing data is because the way this algorithm works uses statistical and probability methods in predicting future results. The results of calculations using the nave Bayes algorithm based on the specified training data show that educators at the junior high school level are ready for the online learning process.